Understanding disagreement within the majority about action to atone for past wrongs - Hartley, Lisa; McGarty, C.; Donaghue, N. (Wiley-Blackwell Publishing Inc., 2013)
Policies atoning for past wrongs against minority groups are often contested within the majority. During the year after the apology to the Indigenous Australian Stolen Generations, predictors of non-Indigenous (majority) collective action intentions focusing on support or opposition to reform reconciliation policies (Study 1, N = 206) and compensation to the Stolen Generations (Study 2, N = 215; Study 3, N = 298) were examined. Action was analyzed as a function of national identity, opinion-based group identity, group-based guilt, political orientation, and collective efficacy. Opinion-based group identification was an independent predictor of action for all groups except for anti-compensation, where efficacy strongly predicted action. Findings highlight opinion-based groups' role in capturing the fault lines of disagreement within majority groups.